2018
DOI: 10.1080/1463922x.2017.1381776
|View full text |Cite
|
Sign up to set email alerts
|

The power of collective intelligence in a signal detection task

Abstract: A novel spatial display for a classic signal detection problem was tested in an experiment with 30 naive volunteers and 2 experts, measuring the signal detection properties of a spatially organised display compared with temporally organised display. The collective performance of committees was also measured. The spatial display was quantitatively and qualitatively superior, resulting in a 4.6% increase in correctness of classifications and a 30.5% decrease in miss percentages. Qualitatively, 83% of participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Signal-detection research suggests that researchers should explore the possible benefits of using a larger number of reviewers to assess submitted manuscripts. Cummings and Quimby (2018) found that combining multiple novice raters’ judgments in a standard signal-detection task yielded more accurate classification decisions than were yielded by individual expert raters (a phenomenon they termed “the power of collective intelligence”). Consistent with these results, Herron (2012) found that the predictive validity of medical journal article evaluations provided by nonexpert readers actually exceeded that of expert readers when a large number of nonexpert ratings were obtained.…”
Section: Signal Detection Self-presentation and Manuscript Review: Pr...mentioning
confidence: 99%
“…Signal-detection research suggests that researchers should explore the possible benefits of using a larger number of reviewers to assess submitted manuscripts. Cummings and Quimby (2018) found that combining multiple novice raters’ judgments in a standard signal-detection task yielded more accurate classification decisions than were yielded by individual expert raters (a phenomenon they termed “the power of collective intelligence”). Consistent with these results, Herron (2012) found that the predictive validity of medical journal article evaluations provided by nonexpert readers actually exceeded that of expert readers when a large number of nonexpert ratings were obtained.…”
Section: Signal Detection Self-presentation and Manuscript Review: Pr...mentioning
confidence: 99%